The Metabolic Syndrome Puzzles; Possible Pathogenesis and Management - Marzoog, Basheer A. (Current Diabetes Reviews, 2023)
Background and Aims: Metabolic syndrome is a multifactorial pathophysiological process with complicated homeostatic disorders that arise from various systematic metabolic defects. Various theories underlie the development of metabolic syndrome but are fully not understood. Methods: Revising PubMed and Scopus literature data on metabolic syndrome pathogenesis and management. Results: The most accepted hypothesis is that a cluster of risk factors combined to obtain a truly metabolic syndrome. The pathophysiology of the metabolic syndrome depends on the underlying development path due to insulin resistance or chronic inflammation and is usually combined with neurohormonal disturbance. Meanwhile, these defects can be inherited via loss of function of certain genes that lead to severe obesity, early diabetes, or severe insulin resistance (with or without lipodystrophy). Chronic inflammation is also a driver of metabolic syndrome. Lifestyle is still the therapy of choice in managing metabolic syndrome, but unfortunately, during the lockdown, most people could not reserve a healthy regime; therefore, it can also be referred to as a pandemic with COVID-19. Conclusions: This powerful illustration shows how defects in specific encoded proteins located predominantly in the brain, pancreatic beta-cell, muscle, or fat give rise to these distinct components of the metabolic syndrome. Primarily, obesity and its sequela are the initiators of metabolic syndrome. The presence of metabolic syndrome increases the risk and severity of other pathologies' emergence, even in non-related metabolic syndrome diseases such as COVID-19. The article provides new insights into the pathogeneses and management of the metabolic syndrome.
Keywords: syndrome X